2019
DOI: 10.3390/app9142837
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Analysis and Energy Dispersion X-ray Microanalysis to Evaluate the Effects of Decontamination Chemicals and Heat Sterilization on Implant Surgical Drills: Zirconia vs. Steel

Abstract: Background: Drills are an indispensable tool for dental implant surgery. Today, there are ceramic zirconium dioxide and metal alloy drills available. Osteotomy drills are critical instruments since they come in contact with blood and saliva. Furthermore, they are reusable and should be cleaned and sterilized between uses. Depending on the material, sterilizing agents and protocols can alter the surface and sharpness of implant drills. The hypothesis is that cleaning and sterilization procedures can affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…One of the major reasons for these is the release of microparticles of steel, which threaten and induce reaction in bone or soft tissues. The results showed in the present study confirm those of a previous one [4]. However, this work adds further information regarding the effects of the disinfection agents on the drills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One of the major reasons for these is the release of microparticles of steel, which threaten and induce reaction in bone or soft tissues. The results showed in the present study confirm those of a previous one [4]. However, this work adds further information regarding the effects of the disinfection agents on the drills.…”
Section: Discussionsupporting
confidence: 90%
“…Zirconia is a good material used in implantology for its good aesthetic properties and biocompatibility [2]. In dentistry, zirconia is largely used for implant abutment and superstructure production [3] because of its strength, durability, corrosion resistance and response to disinfection and sterilizing agents [4].…”
Section: Introductionmentioning
confidence: 99%
“…This good result achieved thanks to the marginal fit, which is critical for the success and longevity of a dental restoration [26]. The protocol adopted in this clinical trial leads to a substantial and advantageous reduction in costs and treatment times; it is supported by a high, long-term prognosis that, according to the studies carried out, ranges from 92 to 100% [19][20][21]. In fact conventional casting techniques are technically difficult for producing a Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The success of an implant surgery depends on the bone and soft tissue healing after the process of implant site preparation [2,21]. During healing and function of a prothesis the bacterial adhesion is very important for a high success of an implant [22].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous histological studies conducted both in vitro and in vivo have shown that ultrasonic microvibrations minimize trauma during the cutting action [5]. As a result, bone healing is much faster from both histological and histochemical points of view [6][7][8].…”
Section: Introductionmentioning
confidence: 99%